2023
DOI: 10.1177/09697330231202233
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress, psychological capital, and burnout in registered nurses

Bowen Xue,
Shujin Wang,
Dandan Chen
et al.

Abstract: Aims This study aimed to explore the relationship among moral distress, psychological capital, and burnout in registered nurses. Ethical consideration The study was approved by the Ethics Committee of the School of Nursing, Hangzhou Normal University (Approval no. 2022001). Methods A cross-sectional descriptive survey was conducted with a convenience sample of 397 nurses from three Grade-A tertiary hospitals in Zhejiang Province, China. Participants completed demographic information, the Nurses’ Moral Distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For example, confident people believe more in their abilities, thus having more motivation to overcome difficulties; Optimistic people are more likely to see the positive side of problems and reduce negative emotions. Psychological capital and emotional exhaustion are interdependent (Xue et al, 2023a, b). Emotional exhaustion may weaken an individual's psychological capital, and lower psychological capital may also make it easier for individuals to experience emotional exhaustion (Xue et al, 2023a, b).…”
Section: The Predictive Indicators Of Trajectories Of Emotional Exhau...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, confident people believe more in their abilities, thus having more motivation to overcome difficulties; Optimistic people are more likely to see the positive side of problems and reduce negative emotions. Psychological capital and emotional exhaustion are interdependent (Xue et al, 2023a, b). Emotional exhaustion may weaken an individual's psychological capital, and lower psychological capital may also make it easier for individuals to experience emotional exhaustion (Xue et al, 2023a, b).…”
Section: The Predictive Indicators Of Trajectories Of Emotional Exhau...mentioning
confidence: 99%
“…Psychological capital and emotional exhaustion are interdependent (Xue et al, 2023a, b). Emotional exhaustion may weaken an individual's psychological capital, and lower psychological capital may also make it easier for individuals to experience emotional exhaustion (Xue et al, 2023a, b). One can try to alleviate emotional exhaustion by improving psychological capital, such as cultivating a positive mindset, exercising stress management skills, and establishing good social support.…”
Section: The Predictive Indicators Of Trajectories Of Emotional Exhau...mentioning
confidence: 99%
“…As nurses gain experience and skills in clinical practice, they gradually build confidence in their abilities. Studies have found that nurses tend to have higher self-efficacy in specific areas such as emergency care and nursing skills (Xue, 2023). This indicates that self-efficacy may vary in different domains and tasks, depending on the nurse's professional knowledge and practical experience.…”
Section: International Journal Of Research Studies In Psychology 45mentioning
confidence: 99%
“…The positive outcomes of such educational interventions appear to last for months, providing improvements in nurses on a wide range of moral and mental health issues such as ethical confidence, moral competence, resilience, work engagement, mindfulness, emotional exhaustion, depression, and anger [39]. As moral distress often fosters burnout and nurses' turnover intention, this creates a mixture of difficult working conditions and burden [40,41]. In addition, burnout can also reduce resilience levels, which in turn affects turnover intention.…”
Section: Introductionmentioning
confidence: 99%